Investigation On Standardization Of Modal Space By Ratio For MDOF Micro-Macro Bilateral Teleoperation Control System - Lee, Jun Wei; Ahmad Zaki, Shukor; Muhammad Herman, Jamaluddin (Canadian Center Of Science And Education, 2016)
This paper presents the research on micro-macro bilateral teleoperation control system of two ink planar manipulator. The micro-macro bilateral control system consists of different size between master and slave system using geared DC-motor. Both master and slave manipulators are actuated by DC-Micromotor attached to planetary gearhead to increase the output torque. In the previous researches the most common actuators used were linear motor and direct-drive DC motors. However, the application of DC motor with gearhead are vast in industry, which need high output force or torque. Thus in this paper, research on micro-macro bilateral teleoperation control system is proposed with the use of gear with the DC-motor. The micro-macro bilateral teleoperation control system provides the human operator with a sense of feel to a micro or macro environment as if it is in the same scale environment. Thus a standardization method is proposed to achieve micro-macro bilateral teleoperation control system. During the experiment, experiment on free motion and contact motion are conducted to validate the proposed setup in bilateral teleoperation control system. The position and torque responses of both master and slave manipulators are observed. The operationality and reproducibility of this proposed system are evaluated through proposed experimental results.